Oral manifestations of Parry-Romberg syndrome - Anto, Irene; Johny, Joseph; Khan, Neena Muneer; Narayanan, Anjhana (Journal of Oral Diagnosis, 2018)
Introduction: Parry-Romberg syndrome (PRS) or Idiopathic hemifacial atrophy is a rare neurocutaneous syndrome, characterized by slowly progressive atrophy located on one side of the face, primarily involving the skin, fat and connective tissue and it becomes stable after certain time period. It exhibits many intraoral and extraoral features. The incidence and the causes of this changes remains unknown. Objective: We present this case report to improve the understanding of this rare condition. Case Report: We present a case of 33 year old male patient who reported to our department with progressive hemifacial atrophy on left side of the face, diagnosed as Parry-Romberg syndrome after clinical and radiographic examination. Conclusion: Parry-Romberg syndrome is a rare condition of progressive deformity of the face with various oral manifestations. It may also involve certain occular and neurological disturbances. The major treatment option is the esthetic management and other symptomatic treatments.